Efeitos da radioterapia na microestrutura do osso cortical : avaliação histológica em coelhos - Rabelo, Gustavo Davi (2009)
Radiotherapy is a well established treatment resource for head and neck cancer, however, can directly affect the bone, which receive high doses of radiation during treatment. The bone tissue when irradiated shows important alterations in their morphology and constitution. The aim of this study was evaluate the effects of radiotherapy in cortical bone of tibia, with quantification of bone matrix and empty osteocytes lacunae, also, with analysis of bone microstructure. Fourteen female rabbits were used, divided into two equal groups: Control and Test. The test group received single dose of 15 Gy cobalt-60 radiation in tibia, bilaterally. After 75 days the animals were sacrificed and 1 cm segment of the tibia were removed, fixed in 10% formalin, decalcified in EDTA and processed for embedding in paraffin. The sections were stained with HE and histologic images were digitized. Images were analyzed through developed algorithms, using SCILAB mathematical environment. Using interactive segmentation was obtained the percentage of bone matrix, area and perimeter of the bone channels and lacunarity. For the percentage of osteocytes and empty lacunae, we used the method of elements counting. The results showed significant difference in percentage of bone by area (p = 0.0003) between the control (96.71%) and irradiated (94.25%) groups. Also, there was significant difference in area (p = 0.0173) and perimeter (p = 0.0437) of the channels and their respective standard deviations (area and perimeter p = 0.0072 p = 0.0039). The lacunarity also showed significant difference (p = 0.014) among the control (16.48) and irradiated (13.80) groups. There was no significant difference in percentage of empty osteocyte lacunae (p = 0.3177). According to results of this study, the radiotherapy causes reduction of bone matrix and modifies the architecture of bone channels network, making it more heterogeneous and less organized.